DESEMPENHO ZOOTÉCNICO E HEMATOLOGIA DE JUNDIARAS (PSEUDOPLATYSTOMA RETICULATUM X LEIARIUS MARMORATUS) SUPLEMENTADOS COM O PREBIÓTICO INULINA - GONÇALVES, N. F.; VEIGA, P. T. N.; OLIVEIRA, E. L.; RODRIGUES, T. A. R.; NUNES, C. S.; CAMPOS, C. M. (ANAIS DO ENIC, 2016)
-